محمد ناصر رئيس وزراء إندونيسيا: السيرة الفكرية والمسيرة السياسية - Solihin, Sohirin Mohammad; Nasser, Youcef (العبيكان للنشر (Obekan Publishing), 2020)
يقدم هذا الكتاب الدكتور محمد ناصر بوصفه أحد القادة المفكرين والسياسيين البارزين في إندونيسيا بخاصة وفي العالم الإسلامي بعامة، ويستعرض خلفيته التعليمية في مجال الدراسات الإسلامية، وقدراته الفائقة في التعاطي مع القضايا الاجتماعية والسياسية التي جلبت له الاحترام. ويؤكد هذا الكتاب على أن الدكتور محمد ناصر كان يعتقد اعتقادًا راسخًا بأهمية تطبيق الشريعة الإسلامية في مناحي الحياة العامة والخاصة، في الوقت الذي كان يعارض بشدة إقامة دولة إسلامية من خلال الحركات الانفصالية، من منطلق أن الحكومة الإسلامية، في رأيه، لا يمكن لها أن تنشأ من دون موافقة الأغلبية؛ مما أدى به إلى اعتبار العملية الديمقراطية وسيلة مشروعة للتعاطي مع تطلعات المسلمين نحو حياة أفضل ومستقبل آمن. *************************************************************************** The book attempts to highlight developmental religious thought of Mohammad Natsir as thinker and reformer of Indonesia. It mainly deals with his thought related to religion and political orientation under the theme ‘Islam as religion and state’ which he subscribed to it throughout his life. Mohammad Natsir did not negate the use of democratic system whenever it brings about the progress and justice. Moreover, the book also discusses the stand of Mohammad Natsir in endorsing what so-called universal values and the concept of nationalism to galvanize the implementation of democracy to serve Muslim majority in Indonesia. In addition, it also sheds more light on his vision with regard to the concept of tolerance across ethnical background and religious adherents. The other aspect it focuses on revealing distinctive thought of Mohammad Natsir related to religious and sociological thought, spirituality and leadership. How far his vision on religious, political and sociological thought are relevant to be applied today in offering solution from political crisis experienced by Muslim parties which is simply due to the shortcoming of program which, at the end, brings about negative impression to Muslims on democracy, humanity and development.